1993
DOI: 10.1111/j.1365-2222.1993.tb00304.x
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of eosinophils in the patch test reaction to aeroallergens in atopic dermatitis: its relevance for the pathogenesis of atopic dermatitis

Abstract: Atopic dermatitis (AD) is considered a T-cell mediated disease. Activated T-cells, mainly of the CD4-subtype, are abundantly present in lesional AD skin. Although not many intact eosinophils are present, deposits of eosinophil derived major-basic-protein (MBP) and eosinophil-cationic-protein (ECP) suggest eosinophil involvement. After patch testing AD patients with aeroallergens, an eczematous reaction develops after 24-48 hr at the site of application. This patch test reaction shows macroscopic resemblance to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 52 publications
1
52
1
Order By: Relevance
“…Recently, IgE-mediated late-phase reaction is thought to be mainly associated with the pathogenesis of AD. [4][5][6] We have established the eczematous skin reaction induced by anti-DNP-IgE antibody and DNFB as an AD model mouse. [7][8][9] STAT6 is known as a regulator of IL-4-dependent immune responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, IgE-mediated late-phase reaction is thought to be mainly associated with the pathogenesis of AD. [4][5][6] We have established the eczematous skin reaction induced by anti-DNP-IgE antibody and DNFB as an AD model mouse. [7][8][9] STAT6 is known as a regulator of IL-4-dependent immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] To clarify the pathomechanism underlying the development of eczematous skin lesions in AD, we established the eczematous skin reaction induced in mice by the intravenous injection of monoclonal anti-dinitrophenyl (DNP)-IgE antibody and subsequent skin testing with 2,4-dinitrofluorobenzene (DNFB) and analyzed these skin reactions as AD mouse model. [7][8][9] We previously demonstrated that mast cells and inflammatory cells other than T cells are thought to play an important role in these IgE-mediated biophasic reaction; 9 however, it remains unclear as to whether Th2-type cytokines, IL-4, IL-5 or IL-13, play a role in the induction of the IgE-mediated reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Histopathological studies shown that the skin lesions of atopic dermatitis are characterized by acanthosis and spongiosis in the epidermis, predominant infiltration by CD1 ϩ cells and activated CD4 ϩ T cells in the dermis, and extensive deposition of eosinophil granule proteins, such as eosinophil major basic protein and eosinophil cationic protein (Leiferman et al, 1985;Bruijnzeel et al, 1993). In addition, serum levels of eosinophil cationic protein have been reported to correlate with the severity of disease (Tsuda et al, 1992).…”
mentioning
confidence: 99%
“…This is supported by a recent study suggesting that Th2 cytokines are involved in eosinophil recruitment. 33,34 Moreover, the suppressed degranulation of mast cells was correlated with the alleviation of the itching and scratching behavior of mice (Fig. 3).…”
Section: Figmentioning
confidence: 81%
“…5,20 Eosinophils play a crucial role in AD symptoms; they secrete eosinophil cationic proteins and thereby induce infiltration of other immune cells into the skin lesions. 33,34 In addition, infiltrated mast cells were degranulated to release histamine and nitric oxide, which promote severe itching. 31,32 Treatment with VU alleviated histopathological AD-like symptoms in dorsal skin, including epidermal thickening (Fig.…”
Section: Figmentioning
confidence: 99%